Empirical analysis on manufacturing energy efficiency of Yangtze River Basin under environmental constraints and its impactors - Lelai Shi; Suhui Liu; Minli Bao (Alexandria Engineering Journal, 2021)
Currently, the manufacturing development in Yangtze River Basin is featured by high energy consumption and high pollution. This consumes lots of energy and creates severe environmental pollution. For the sustainable development of manufacturing, it is necessary to scientifically evaluate the manufacturing energy efficiency of Yangtze River Basin. In this paper, the suitable metrics are firstly selected to evaluate the manufacturing energy efficiency (MEE) under environmental constraints. Then, the panel data 2010–2018 on the manufacturing of the 11 regions of the Yangtze River Basin were taken as the object. On this basis, the MEE in the Belt was analyzed statically and dynamically with the slack-based measure (SBM) model and Malmquist-Luenberger metric, respectively. In addition, the Tobit model was adopted for regression analysis on how various factors affect the Belt MEE. The results show that: the MEEs in the Belt were severe polarized, with significant differences between regions; in most regions, the ML was improved to varied degrees in the sample interval; comparatively, technological progress boasts stronger promoting effect than technical efficiency improvement; the Belt MEE is significantly promoted by technological innovation, foreign trade, and environmental regulation, significantly suppressed by property-right structure and energy price, and not significantly affected by industrial structure or energy structure.